Réponses

2014-02-03T16:29:19+01:00
Démontrer que 1/V3 + 1/V12 = V3/2  (V se lit racine carré de)
Elevons au carré la somme :
(1/V3 + 1/V12)² = (1/V3)² + 2*(1/V3)*(1/V12) + (1/V12)² (identité remarquable)
(1/V3 + 1/V12)² = 1/3 + 2/V(3*12) + 1/12
(1/V3 + 1/V12)² = 4/12 +2/V36 + 1/12
(1/V3 + 1/V12)² = 5/12 +2/6
(1/V3 + 1/V12)² = 5/12 + 4/12
(1/V3 + 1/V12)² = 9/12
(1/V3 + 1/V12)² = 3/4

1/V3 + 1/V12 = V(3/4) = V3/V4 = V3/2

Cocher la bonne réponse
1. (2V7)² = 4*7 = 28 réponse b

2. 2x²-3 = 1
2x² = 1+3
2x² = 4
x² = 4/2
x² = 2 donc x= -V2 et x=V2 réponse c

3. V(294) = V(6*49) = 7V6 réponse b

4.(x-1)²+3v2 = (V2 -1)²+3V2 = 2-2V2 +1 +3V2 = 3+V2 réponse a